Towards quantifying the possible risk in e-commerce interactions for RDSS - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh Khadeer; Dillon, Tharam S. (IEEE, 2007)
By analyzing the possible level of Risk beforehand the initiating agent can make an informed decision of its future course of interaction with an agent. The possible risk in the context of an e-commerce interaction is a multidimensional construct which is the combination of different constituents. In this paper we propose a methodology by which the initiating agent can determine and analyze those constituents in order to ascertain the possible level of risk in interacting with an agent.